Interferensi Elektromagnetik pada Pacu Jantung - Sefri Noventi Sofia; Yoga Yuniadi (The Indonesian Heart Association, 2012)
Increasing numbers of permanent pacemaker implantation in Indonesia raise the needs of electromagnetic interference (EMI) knowledge. EMI potentially result in pacemaker malfunction or failure that endangered the patient. This review discuss EMI sources that exist around patient daily live such as magnetic resonance imaging (MRI) examination, cellular phone, microwave oven, metal detector gate, elctrical cardioversion etc.